The mediating effect of attitude on direct and indirect determinants of Internet banking usage in Malaysia - Ahmad Kamal, Sindin (2016)
Internet banking in Malaysia has been in existence for more than two decades. However, there is still lack of studies in discovering the aspects of attitude and behavior of the retail banking customers towards the adoption of the internet banking services. Therefore, this study aims to investigate the determinants of the internet banking usage from the angle of attitude and behavior of these customers in the internet banking usage. This study employed the Technology Acceptance Model by Davis as the underpinning theory and further enhanced it to the Extended Technology Acceptance Model by taking into account factors such as trust, internet self-efficacy, and subjective norm as the additional predictors of internet banking usage via the mediating effect of attitude towards usage. The study setting was based on five top commercial banking in Malaysia and systematic random sampling of data collection was done through households via self–administered questionnaire and analysis was done by using the structural equation modelling as the statistical tool. The findings show that perceived ease of use and attitude have a positive significant effect on internet banking usage while perceived usefulness and internet self-efficacy have a positive impact on attitude. The findings further reveal that perceived usefulness and internet self-efficacy mediate through attitude on the internet banking usage while trust, perceived ease of use, and subjective norm do not mediate through attitude on the internet banking usage. These results are immeasurably valuable to practitioners for managing and executing their marketing strategy. Furthermore, it contributes and enriches knowledge pertaining to the predictors of internet banking usage.